The Future of Public Policy Post COVID-19 - Naglaa FATHY EL DESSOUKY (Communications of International Proceedings, 2022)
This research aims to study and provide deep insights into the future of public policy post-COVID-19. A thorough literature review revealed that the public policy field is witnessing a paradigm shift that is directly coupled with the reality of today. The paper attempted to present the major global issues and the challenges they may impose on the academic field of public administration and public policy, the contemporary shift related to the public policy cycle, and the epistemology of public policy as well as its role in influencing the future orientation of research. The research concluded that there are many challenges facing the field of public policy due to the rapid and successive development of contemporary issues at the local, regional, and international levels.
Keywords: Public Policy; COVID-19; Global Issues; Paradigm Shift; Epistemology.